(untitled) (Annals of Medical Research, 2021)
Aim: This study investigated the effect of the rehabilitation received in individual (private) and state institutions on the results with regard to the patients undergoing arthroscopic repair due to isolated supraspinatus tear.Material and Methods: Fifty-eight patients, who underwent arthroscopic repair in the Orthopaedics and Traumatology clinic of the University betw Selçuk University between 2013 and 2015 were examined retrospectively and the preoperative and postoperative constant scores were calculated. Results: 15 of the 37 patients included in the study were rehabilitated in individual institutions, while 20 patients in state institutions and two patients were monitored by a home exercise program. The mean postoperative constant score was found 73 in the group who received individual rehabilitation, and 65.6 in the patients who were rehabilitated in state institutions (p 0.05); in the former, a significantly higher score was obtained.Conclusion: We consider that receiving individual rehabilitation after arthroscopic repair will be more advantageous in terms of pain and functional recovery.Keywords: Supraspinatus; arthroscopy; rehabilitation.